Implementasi Good Governance sebagai Upaya Penguatan Otonomi Daerah di Indonesia - Neneng Saputri; Desta Prianti; Nugraha Gading Priandana; Ichwan Karunia; Aftesia Labira Lauli; Ira Kurniawan; Mila Agustin; Sella Agri Bardana; Rima Fadhilatunnisa; Ana Mentari; Febra Anjar Kusuma (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The implementation of good governance plays a crucial role in strengthening regional autonomy in Indonesia, particularly following the enactment of decentralization policies. This study aims to describe the relationship between the application of good governance principles and the enhancement of local government authority. Using a descriptive qualitative method based on a literature review, this research examines various sources including national journals, research reports, policy documents, and other relevant academic works. The results indicate that the principles of good governance accountability, transparency, participation, rule of law, effectiveness, and efficiency significantly contribute to fostering more responsive, accountable, and service-oriented regional autonomy. However, several challenges persist, such as limited bureaucratic capacity, fiscal disparities, weak supervision systems, and bureaucratic cultures that have not fully supported transparency. The study concludes that good governance and regional autonomy mutually reinforce each other; autonomy provides space for innovation, while good governance ensures that authority is exercised effectively and responsibly. Strengthening digital public services, bureaucratic reform, public oversight, and institutional capacity-building are recommended to support sustainable regional autonomy.